Resiko Usahatani Kopi di Kabupaten Lampung Barat - Fikri Syahputra (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The plantation sub-sector plays an essential role in maintaining the stability of food security and as a provider of raw materials for national industry. Coffee plants are a commodity that can grow optimally if cultivated in tropical areas. Lampung Province is one of the largest coffee producers in Indonesia. Production in 2022 will reach 118,043 tons. Most coffee farmers in the region form partnerships with companies by forming farmer groups. This research aims to (1) determine the difference in income between company-partner coffee farming and company-non-partner coffee farming and (2) determine the difference in the risk level of company-partner coffee farming and company-non-partner coffee farming. This research method is a survey method. This method is implemented by direct observation of a research object. This research was carried out in 2022. The location was selected based on West Lampung Regency being the largest coffee-producing area in Lampung. The total respondents were 67 coffee farmers from the Sumberjaya sub-district area. Sumberjaya subdistrict was chosen with consideration because it has coffee farmers who are partners and not partners with companies. The respondents were 49 coffee farmers who partnered with a company (PT. Indocafco) and 18 respondents who did not partner with a company. The research respondents were used as a whole (Arikunto, 2006) based on a population <100 (Nazir, 2014). Research data analysis consists of the coffee farming business income of company partners and non-partner farmers and risk analysis of the coffee farming business of company partners and non-partner farmers. The research results found that the total income of the company's partner coffee farms was greater than that of the company's non-partner coffee farms. Partner and non-partner farming is worth pursuing based on the R/C ratio value indicator >1. The coffee farming business of company partners and non-partners has potential risk with the coefficient of variation (CV) indicator value> 0.5. The coffee farming of company partners and non-partners can be profitable with the lower limit value indicator (L)>0.